Analysis of Marketing Mix Factors Influencing Handicraft Sales - Dewi Citra Christianda; Eko Jokolelono; Yunus Sading; Andi Herman Jaya; Musdayati Musdayati (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The MSME sector plays a crucial role in Indonesia's economy. In Palu City, MSMEs absorb 97% of Palu City's workforce, making the handicraft industry vital for economic growth and cultural preservation. Mantikulore sub-district houses 11 handicraft industries, primarily ebony-based products, but faces competitive challenges in product quality, pricing, location, and promotion. Research indicates that product quality and business location significantly influence consumer purchasing decisions, highlighting the need to understand these factors for strategic industry development. The primary objective of this study is to examine the various elements that impact the selling of handicrafts within Mantikulore sub-district in Palu City. The methodology employed in this research involves descriptive analysis, with data being gathered through a quantitative survey utilising a Likert scale and the Spearman rank correlation test. The findings from the analysis indicate that the quality of the product has a notably strong connection to sales, displaying a correlation coefficient of 0.80 (p < 0.05). Additionally, factors such as pricing and location also play a significant role in driving sales, with correlation coefficients of 0.77 (p < 0.05) and 0.74 (p < 0.05) respectively.  Conversely, it was found that promotional activities do not contribute significantly to boosting sales, as indicated by a coefficient of -0.067 (p > 0.05), suggesting that the current promotional strategies in place are ineffective in increasing sales.